Observations and Perceptions of Diseases in Hankou by Customs Medical Officers in the Mid-to-Late Nineteenth Century: An Examination Centered on the Customs Medical Bulletin - LI Hengjun, (Journal of Research for Christianity in China (JRCC), 2025)
This paper primarily draws on data from customs medical reports to examine the observations and understanding of Chinese customs medical officers regarding the geography, climate, sanitary conditions, and disease patterns in the Hankou region during the mid-to-late 19th century. Unlike previous studies, the focus here is not on the statistical analysis and classification of specific diseases. Instead, it aims to delve deeper into the medical knowledge framework underlying these disease perceptions and explore the connections between the construction of medical knowledge and broader socio-historical contexts such as modern Western colonialism and the rise of tropical medicine.
Keywords: Customs Medical Bulletin, Hankou, Customs Medical Officer